2008
DOI: 10.1128/ec.00147-08
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Induced Cell Death Is Mediated by Ceramide Synthesis in Neurospora crassa

Abstract: The combined stresses of moderate heat shock (45°C) and analog-induced glucose deprivation constitute a lethal stress for Neurospora crassa. We found that this cell death requires fatty acid synthesis and the cofactor biotin. In the absence of the cofactor, the stressed cells are particularly sensitive to exogenous ceramide, which is lethal at low concentrations. When we extracted endogenous sphingolipids, we found that unique ceramides were induced (i) by the inhibitory glucose analog 2-deoxyglucose and (ii) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 82 publications
(90 reference statements)
3
31
0
Order By: Relevance
“…The inducible strain PB20i had a very similar viability to the lac‐1 KO bd strain previously analyzed (Tables 2 and 5), confirming the viability effect of the double mutant, but induction of lac‐1 + shortened the estimated median chronological lifespan to just 7.5 days. While there may be other explanations for this sharp decrease in viability, such as interference between the induced lac‐1 + transcript and other transcriptional units, there is interesting evidence that the expression of ceramide synthases, such as lag‐1 or lac‐1 , and the level of phytoceramide production may have been optimized by natural selection to a specific level over time, and any other level of ceramide production may be deleterious (Plesofsky et al., 2008) (Jiang et al., 2004). …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The inducible strain PB20i had a very similar viability to the lac‐1 KO bd strain previously analyzed (Tables 2 and 5), confirming the viability effect of the double mutant, but induction of lac‐1 + shortened the estimated median chronological lifespan to just 7.5 days. While there may be other explanations for this sharp decrease in viability, such as interference between the induced lac‐1 + transcript and other transcriptional units, there is interesting evidence that the expression of ceramide synthases, such as lag‐1 or lac‐1 , and the level of phytoceramide production may have been optimized by natural selection to a specific level over time, and any other level of ceramide production may be deleterious (Plesofsky et al., 2008) (Jiang et al., 2004). …”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have suggested that phytoceramide is expressed at an optimum level within the conidia of N. crassa (Plesofsky et al., 2008). We predict that the optimum level of phytoceramide production shifts based on the activity of phytoceramide‐producing genes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations